2018
DOI: 10.1590/1519-6984.180789
|View full text |Cite
|
Sign up to set email alerts
|

More than two decades after the introduction of Limnoperna fortunei (Dunker 1857) in La Plata Basin

Abstract: The golden mussel, Limnoperna fortunei, is an Asian freshwater bivalve introduced in South America in the beginning of the 1990's, probably through ballast water releases in La Plata River estuary. It dispersed north through Paraná, Uruguay and Paraguay Rivers. The study evaluated the macroscale (18° to 34° S; 45° to 60° W) distribution of L. fortunei (larval stages) in the main rivers and reservoirs of La Plata Basin. Samplings were performed through 68 µm vertical plankton net hauls. Limnological variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
5
18
2
2
Order By: Relevance
“…Water temperature is known to be the main abiotic factor for L. fortunei development because it is critical to its vital activities, including reproduction, growth, and survival(Cataldo et al, 2012;Perepelizin & Boltovskoy, 2015). The larval density recorded here was higher than the highest recorded byPessotto and Nogueira (2018) in samples from 48 sites in the La Plata Basin, including the Paranapanema River. These authors observed the highest value in the Río de la Plata estuary at 60,000 larvae/m 3 in the summer of 2010.Boltovskoy, Correa, Sylvester, and Cataldo…”
contrasting
confidence: 73%
“…Water temperature is known to be the main abiotic factor for L. fortunei development because it is critical to its vital activities, including reproduction, growth, and survival(Cataldo et al, 2012;Perepelizin & Boltovskoy, 2015). The larval density recorded here was higher than the highest recorded byPessotto and Nogueira (2018) in samples from 48 sites in the La Plata Basin, including the Paranapanema River. These authors observed the highest value in the Río de la Plata estuary at 60,000 larvae/m 3 in the summer of 2010.Boltovskoy, Correa, Sylvester, and Cataldo…”
contrasting
confidence: 73%
“…In relation to the dispersion potential of L. fortunei , Pessotto & Nogueira () found in the La Plata basin, more than 20 years after its introduction in this basin, high larval densities in all the main sub‐basins, with the species reaching lower latitudes in the upper Paraná sub‐basin, in a counter‐flux displacement greater than 2,000 km. Considering the history of the mussel invasion on the Paraná River, Avelar, Martim, and Vianna () revealed the presence of the mussel in this river in 2002, downstream of the city of Rosana (22°32′56.9″S–53°2′48″W), characterizing the population as young and in full process of colonization.…”
Section: Discussionmentioning
confidence: 95%
“…In Brazil, the occurrence of golden mussel was first reported at the end of 1998 and beginning of 1999, in the State of Rio Grande do Sul, in the Jacuí River delta, and in the Guaíba Lake basin, respectively (Mansur, Richinitti, & Santos, ; Mansur et al, ). Recent studies have demonstrated a wide territorial distribution of this species, which encompasses several South American river basins, such as the basins of rivers Paraguay, Paraná, Uruguay, La Plata (Pessotto & Nogueira, ), and even in water bodies in the Northeast region of Brazil, such as the São Francisco River Basin (Barbosa et al, ). In the Paranapanema River, a tributary of the Paraná River, the first occurrence of the species was recorded in 2006, in the Canoas I reservoir (Garcia, Orsi, Casimiro, & Kurcheski, ).…”
Section: Introductionmentioning
confidence: 99%
“…The golden mussel L. fortunei attracts the full attention of scientists and stakeholders as an invasive species rapidly spreading in South America, Japan, and Hong Kong, and causing large economic and environmental impacts (Morton, 1973(Morton, , 2015Pessotto & Nogueira, 2018;Ricciardi, 1998). Although a number of molecular studies were already focused on this species, including the whole genome sequencing (De Paula et al, 2020;Uliano-Silva et al, 2018), any DNA sequence data on its populations from the Mekong Basin were not available.…”
Section: Taxonomy and Evolutionary Biogeography Of The Freshwater Mytilidaementioning
confidence: 99%